Physical and psychosocial side-effects of brachytherapy: a questionnaire survey - Ferenc, Sara; Rzymski, Piotr; Skowronek, Janusz; Karczewski, Jacek (Journal of Contemporary Brachytherapy, 2015)
Purpose : Brachytherapy (BT) plays an important role in cancer treatment. Like any other medical therapy it may, however, induce side effects whose recognition can affect the patient’s quality of life. Therefore, the present study evaluated the frequency and severity of physical and psychosocial adverse effects of BT. Material and methods : Patients (n = 70) undergoing high-dose-rate (HDR) BT or low-dose-rate (LDR) of head and neck, breast, and prostate cancers were interviewed face-to-face at the end of their course of treatment. Interviews concerned the occurrence of 35 physical (dermatological, gastroenterological, neurological, ocular, pulmonological, and urological) and 10 psychosocial side effects of BT. Results : A high percentage of patients reported that BT decreased their life satisfaction (54.3%), sense of security (41.4%), and self-esteem (34.3%). The highest frequency of gastroenterological and urological symptoms was reported by prostate cancer patients. Cigarette smoking increased the frequency of nausea, dyschezia, and weight loss. Overweight patients were characterized by an increased rate of urinary incontinence and dyschezia, as well as more pronounced decrease of self-esteem and sense of security following BT treatment. Conclusions : These findings are not only highly relevant to the way patients can be prepared for the therapy but also have a bearing on ways to minimize the number and severity of BT side effects.